2021
DOI: 10.3390/s21134513
|View full text |Cite
|
Sign up to set email alerts
|

Features and Practicability of the Next-Generation Sensors and Monitors for Exposure Assessment to Airborne Pollutants: A Systematic Review

Abstract: In the last years, the issue of exposure assessment of airborne pollutants has been on the rise, both in the environmental and occupational fields. Increasingly severe national and international air quality standards, indoor air guidance values, and exposure limit values have been developed to protect the health of the general population and workers; this issue required a significant and continuous improvement in monitoring technologies to allow the execution of proper exposure assessment studies. One of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 109 publications
0
26
0
Order By: Relevance
“…The standard method to measure PM concentrations is the gravimetric method, that is, sampling PM on filters and weighing them before and after the collection, and it is usually presented in daily values as the PM collection occurs in a period of nominally 24 h [67]. For continuous monitoring, laser scattering processes are one of the most used techniques to measure PM concentrations [68].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The standard method to measure PM concentrations is the gravimetric method, that is, sampling PM on filters and weighing them before and after the collection, and it is usually presented in daily values as the PM collection occurs in a period of nominally 24 h [67]. For continuous monitoring, laser scattering processes are one of the most used techniques to measure PM concentrations [68].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…NGMSs ("next-generation" monitors and sensors), which refers to "miniaturized" and/or "wearable" sensors and/or monitors, are expected to make the exposure and risk assessment in occupational settings more convenient and comprehensive [4]. A recent systematic review [8] analyzed the use of NGMSs in occupational hygiene for airborne hazards: results outlined that these applications are less frequent than in environmental hygiene, and this is probably due to the fact that policy-and legislation-based decisions requires a high-level detection limit for data, precision, accuracy, and completeness [9]. Despite that, NGMSs devices can provide new resources in the occupational-safety and health-management fields [10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Problem Statementmentioning
confidence: 99%
“…The rise of low-cost personal air monitoring devices has enabled scientists to involve citizens in air quality monitoring programmes. The small size of these devices, their low cost, high temporal resolution for data capture and internet connectivity for remote access facilitates their use in large scale studies of multiple stressors [1,2]. It is known that personal exposure to air pollution depends on individual trajectories and activities [3], and exposure studies have demonstrated the need for data with a high spatio-temporal resolution in order to obtain a rigorous personal exposure assessment [4,5].…”
Section: Introductionmentioning
confidence: 99%